Myeloid differentiation factor 88 (Myd88) is involved in the innate immunity of black carp (Mylopharyngodon piceus) defense against pathogen infection. Issue 94 (November 2019) - Zhang, Xueshu; Xu, Xiaoyan; Shen, Yubang; Fang, Yuan; Zhang, Jiahua; Bai, Yulin; Gu, Shuting; Wang, Rongquan; Chen, Tiansheng; Li, Jiale
Abstract: Myeloid differentiation factor 88 ( MyD88 ) is an important transduction protein in the Toll-like receptor signaling pathway. In this study, we identified the cDNA of the MpMyD88 gene in black carp. We found that MpMyD88 was widely distributed in the tissues tested and showed significant immune responses both in vitro and in vivo after stimulation with bacterial and pathogen-associated molecular patterns. After MpMyD88 overexpression/silencing, proinflame-matory cytokines (TNF-α, IFN-α, IL-6, and IL-8) also showed significant up-regulation/down-regulation. Moreover, we found that the antibacterial ability of cells over-expressing MpMyD88 was significantly stronger than that of control cells, while that of silenced MpMyD88 was significantly lower than that in control cells. Besides, we found that the overexpression of MpMyD88 significantly increased the activity of NF-κB. These results indicate that MpMyD88 plays an important role in the innate immune response. Highlights: The MyD88 gene ( MpMyD88 ) of black carp was cloned. The functional domains in MpMyD88 were highly conserved. MpMyD88 is expressed in all tested tissues of the black carp. Overexpression of MpMyD88 activated the immune gene and NF-kB signaling pathway of black carp to resist pathogen infection. MpMyD88 plays an important role in the innate immunity of black carp.